2015
DOI: 10.1371/journal.pgen.1005373
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Phenomics Identifies Primary and Fine-Tuning Roles for CRKs in Responses Related to Oxidative Stress

Abstract: Cysteine-rich receptor-like kinases (CRKs) are transmembrane proteins characterized by the presence of two domains of unknown function 26 (DUF26) in their ectodomain. The CRKs form one of the largest groups of receptor-like protein kinases in plants, but their biological functions have so far remained largely uncharacterized. We conducted a large-scale phenotyping approach of a nearly complete crk T-DNA insertion line collection showing that CRKs control important aspects of plant development and stress adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
191
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(201 citation statements)
references
References 87 publications
8
191
1
1
Order By: Relevance
“…Cys-rich receptor-like kinases (CRKs) have been shown to be involved in signaling during biotic and abiotic stresses that generate apoplastic ROS, and CRKs are potential candidates for apoplastic ROS perception and signaling (Bourdais et al, 2015). Among genes coding for CRKs, 47 and nine were up-regulated in lignin-forming conditions and when H 2 O 2 was scavenged, .…”
Section: Apoplastic H 2 O 2 Production and Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Cys-rich receptor-like kinases (CRKs) have been shown to be involved in signaling during biotic and abiotic stresses that generate apoplastic ROS, and CRKs are potential candidates for apoplastic ROS perception and signaling (Bourdais et al, 2015). Among genes coding for CRKs, 47 and nine were up-regulated in lignin-forming conditions and when H 2 O 2 was scavenged, .…”
Section: Apoplastic H 2 O 2 Production and Signalingmentioning
confidence: 99%
“…8D). CRK expression has been shown to be modulated in response to ROS-and cellular redox state-related stresses (Lehti-Shiu et al, 2009;Wrzaczek et al, 2010;Bourdais et al, 2015). Moreover, CRKs are thought to be involved in cellular redox and apoplastic ROS sensing by the presence of conserved Cys residues in their apoplastic domain.…”
Section: The Apoplastic Redox State Influences Cellular Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The DUF26 domain possesses a conserved C-X 8 -C-X 2 -C motif (Ohtake et al, 2000;Chen, 2001). The Cys residues in each DUF26 domain are predicted to form two Cys bridges, which are hypothesized to be targeted for apoplastic redox modification (Bourdais et al, 2015). In the Arabidopsis genome, there are 46 predicted CRKs, eight plasmodesmata-located proteins (PDLPs), and more than 50 Cys-rich repeat secretory proteins that possess DUF26 domains (Chen, 2001;Amari et al, 2010;Bourdais et al, 2015).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that Arabidopsis CRKs are transcriptionally induced in response to abiotic stresses, including salicylic acid, ozone, UV light, salt, and drought treatments (Chen et al, 2003(Chen et al, , 2004Wrzaczek et al, 2010;Bourdais et al, 2015;Yeh et al, 2015). A subset of CRKs is strongly induced in response to pathogens and PAMP treatment (Wrzaczek et al, 2010;Bourdais et al, 2015).…”
mentioning
confidence: 99%